2020
DOI: 10.1186/s42466-020-00058-0
|View full text |Cite
|
Sign up to set email alerts
|

Changed functional connectivity at rest in functional illiterates after extensive literacy training

Abstract: Background About 6.2 million adults in Germany cannot read and write properly despite attending school for several years. They are considered to be functional illiterates (FI). Since the ability to read and write is crucial for being employed and socially accepted, we developed a special literacy training to overcome these deficits. Methods In this study, we investigate training-related changes in intrinsic functional connectivity (iFC) at rest in a group of 20 FI and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In fact, the answer is no. Several studies based on alphabetic language reading have found that this pathway plays an important role ( Alcauter et al, 2017 ; Hancock et al, 2017 ; Mohammadi et al, 2020 ). Third, is fronto-striatal connectivity stronger in Chinese reading than in alphabetic language reading?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the answer is no. Several studies based on alphabetic language reading have found that this pathway plays an important role ( Alcauter et al, 2017 ; Hancock et al, 2017 ; Mohammadi et al, 2020 ). Third, is fronto-striatal connectivity stronger in Chinese reading than in alphabetic language reading?…”
Section: Discussionmentioning
confidence: 99%
“…The study of illiteracy training belongs to the early stage of reading development, so the thalamus is the most prominent and easy to discover. For example, another study of training based on functional illiteracy found that although the connectivity strength of the fronto-striatal and thalamo-visual pathways was significantly lower in the illiterate group than in the control group, only the thalamic network, not the striatum network, was enhanced after a short training session ( Mohammadi et al, 2020 ). This finding suggests that the thalamic network is more likely to be increased early in training, while the striatum network requires more training time to become more involved in reading ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations